Proportional-integrative controller design of Pneumatic system using particle swarm optimization - Osman, K. (2015)
Pneumatic systems are well known for their advantages, simplicity and can be applied in various industrial applications. This paper presents a comparative study of tuning methods on Proportional-Integral (PI) controller for position control performance both in simulation and in real system. A PI controller designed by optimization with the Particle Swarm Optimization (PSO) algorithm is proposed and its output is compared with the Ziegler-Nichols (Z-N) formula and manual (trial and error) results. Performance assessment of the tuned controllers was performed in MATLAB Simulink. It was observed that the controller designed using PSO gives better results and performance compared to the Z-N formula and manual tuning in simulation and real-time.